Optimalisasi Inventory Management Material Aluminium Menggunakan Metode Economic Order Quantity (EOQ) dan Reorder Point (ROP) pada Perusahaan Rekondisi Transformator Sidoarjo - Moch Fatur Angga Pratama; Moch Bahrul Ulum; Gian Dwi Hermawan; Muhamad Abdul Jumali (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
Effective inventory control plays an important role in supporting the transformer repair process. PT Rekondisi Transformator Sidoarjo still manages aluminum material procurement based on operational needs, increasing the risk of stockouts. This study aims to analyze aluminum inventory management using the Economic Order Quantity (EOQ), Reorder Point (ROP), and Total Inventory Cost (TIC) methods. A qualitative approach with a case study design was employed. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model supported by EOQ, ROP, and TIC calculations. The results indicate an optimal order quantity of 1,555 kg, a purchasing frequency of approximately two orders per year, and an ROP value of 58.2 kg. The implementation of EOQ and ROP provides a more systematic inventory control system, reduces the risk of stockouts, and supports the continuity of the transformer repair process